Prevalence of GCKR rs1260326 Variant in Subjects with Obesity Associated NAFLD and T2DM: A Case-Control Study in South Punjab, Pakistan - Tayyaba Nisar; Kashan Arshad; Zahid Abbas; Maira Ali Khan; Sohail Safdar; Rehan Sadiq Shaikh; Ali Saeed (Journal of Obesity)
The glucokinase regulatory protein (GCKR) regulates glycogen metabolism and insulin secretion, and the GCKR rs1260326 is a putative single nucleotide polymorphism (SNP) associated with metabolic disorders including nonalcoholic fatty liver disease (NAFLD) and type 2 diabetes mellitus (T2DM). This study was conducted to investigate the genetic association of the GCKR rs1260326 in NAFLD and T2DM in our population. NAFLD (n = 103), T2DM (n = 100), and control (n = 100) samples were collected and genotyped for GCKR rs1260326 by tetra-arm PCR. The genetic variant GCKR rs1260326 was significantly linked with NAFLD and T2DM, while the GCKR rs1260326 was significantly associated with the progression of obesity only in NAFLD subjects. The frequency of the C allele (mutant) was higher in both NAFLD (f = 0.69) and T2DM (f = 0.66) subjects as compared to healthy controls of NAFLD (0.52) and T2DM (f = 0.32). The frequency of the C allele was also positively linked with the progression of obesity in both diseases. The frequency of the C allele was 0.66, 0.67, and 0.74 in NAFLD normal weight, overweight, and obese subjects, respectively, while the frequency of the C allele was 0.60, 0.60, and 0.74 in T2DM in normal weight, overweight, and obese subjects, respectively. Homozygous mutant (CC) was 53% in both NAFLD and T2DM subjects, while heterozygous mutant (CT) was 15.53% in NAFLD and 22% in T2DM subjects. Wild-type allele (TT) was 31.06% in NAFLD and 25% in T2DM subjects. In conclusion, the GCKR rs1260326 is a highly prevalent SNP in NAFLD and T2DM subjects, which possibly contributed to obesity, insulin resistance, and metabolic disorders in our population.